Odontogenic fibromyxoma and odontogenic cyst in an eight-year-old boy: three-year follow-up - Hossein Shahoon; Mostafa Esmaeili; Maryam Nikhalat; Ensie Farokhi (Tabriz University of Medical Sciences, 2009)
Odontogenic fibromyxoma is a rare and locally-invasive benign neoplasm found exclusively in the jaws. It has the potential for extensive bony destruction and extension into the surrounding structures.
In the presented case, radiographic and histological features as well as the treatment and follow-up of odontogenic fibromyxoma accompanying odontogenic cyst of mandible in an 8-year-old boy are discussed.